Centro arquitectónico sostenible de capacitación y emprendimiento (2021)
Thermal comfort inside spaces in hot humid climates is a factor that is essential today to be able to inhabit a space, but unfortunately that need is being satisfied with active strategies, such as air conditioning and this is the architectural problem that it presents. Barrancabermeja. The absence of passive bioclimatic strategies in the design as such of the architecture, makes the use of air conditioners causing high energy consumption and also generating a significant negative environmental impact. Likewise, there is the problem of the high unemployment rate caused by the economic downturn due to the high dependence on oil. Having repercussions in the social sphere and damaging the great natural biodiversity with the exploitation of other economic resources such as agriculture, fishing and livestock.